Evaluation of multifunctional properties of graphene based cement composites / Sardar Kashif Ur Rehman - Sardar Kashif , Ur Rehman (2018)
Nanomaterials are being used in the construction industry to improve the microstructural, mechanical and electrical properties of the building material. These nanomaterials are incorporated to overcome the shortcomings of conventional construction materials. Graphene is one of the nanomaterials that has been widely focused due to its extraordinary properties such as huge specific surface area, high intrinsic strength and high electrical transport properties. Nowadays, graphene was found to have a potential to enhance the properties of cement composite. This study evaluates the multifunctional properties of graphene-cement composites (GCC), aiming at the micro-analytical characterization, rheological behavior, mechanical and piezo-resistive properties. In this research, three types of graphene flakes based on surface area and lateral flake thickness were used. Firstly, dispersion efficiency of graphene was examined by UV-vis spectroscopy. Then, GCC were characterized by using Thermogravimetric Analysis (TGA), Fourier Transform Infrared (FTIR) Spectrometry, X-ray Diffraction (XRD) and Field Emission Scanning Electron Microscopy (FESEM). Afterwards, the rheological properties of fresh cement paste with various graphene types, graphene content, shear rate cycles, resting time and geometrical conditions were investigated. The rheological data were fitted by the Bingham model, Modified Bingham model, Herschel-Bulkley model and Casson model to estimate the flow properties of GCC. The effectiveness of these rheological models was expressed by the standard error. Mechanical properties were investigated for graphene cement mortar. Electrical properties of graphene were employed to evaluate the damage-sensing characteristics of GCC. Finally, the practical application of GCC was evaluated by testing the full length reinforced concrete (RC) beam. Various damage levels were induced in RC beam to monitor the response of GCC. Experimental results concluded that 40 min magnetic stirring in combination with 3 min ultrasonication gave the optimum results. Moreover, graphene with the high surface area and less thickness have stable and uniform dispersion. From TGA and XRD results, it was found that more hydration occurred due to graphene. FESEM images showed that graphene flakes with high surface area successfully provide the hindrance to the propagation of cracks; moreover, hydrated cement products grow in an ordered way. Rheological results showed that yield stress and plastic viscosity increased by the addition of graphene flakes with higher flake thickness and more resting time while these values decreased for higher shear rate cycle. Concentric cylinders estimated lower yield stress and standard error as compared to parallel plates. Moreover, non-linear models i.e. Herschel-Bulkley and Modified Bingham were found as best fitted models. In comparison to control sample, the GCC with more flake thickness showed a 30.5% increase in load carrying capacity and 113.5% increase in overall failure strain. It was found that electrical resistivity value for high surface area flakes reduced by 67.8% at the maximum compressive load, and hence GCC can be used to detect the damages in concrete. Graphene cement composite determined the electrical resistivity against various damage levels in an accurate manner in RC beam. In conclusion, GCC has better improved properties and it can successfully predict the response against cracks propagation. The outcome of this study is as a precursory development for smart composites to be utilized as construction materials as well as to monitor the structural health of the concrete structures.